La société comme « système complexe » - Antoine Bernard de Raymond (Revue d'anthropologie des connaissances)
Since the beginning of the 21st century, researchers in the physical sciences have built up a strong capacity to grasp contemporary issues and to set the political agenda. Not only do these categories frame public issues, but they also circulate among other scientific disciplines, thus reshaping their respective epistemologies and methods. This paper examines the interdisciplinary circulation of complexity science and its consequences for economic and social sciences. First, it highlights the characteristics of complexity as a scientific knowledge, and shows how this approach has been able to circulate to the economic sciences as a response to situations of crisis, both epistemic and scientific, such as the financial crisis of 2008. Then, it shows that the translation of a disparate body of knowledge on complexity into a standardized method and approach, namely complex networks, has allowed its more general adoption within the social sciences. Finally, it shows that, while the complex networks approach brings real benefits in terms of understanding disasters and disruptions, it has serious limitations both in terms of data compliance and in terms of the epistemology of systemic events.